Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type - Nagy, Hajnalka; Felföldi, Tamás; Dózsa-Farkas, Klára (Zootaxa, 2018)
One enchytraeid species, proved to be new to science, is described in this paper as Fridericia ventrochaetosa sp. nov. The new species is distinguished from similar species, especially from F. galba (Hoffmeister, 1843), which has almost the same type of spermatheca, on the basis of morphological characters and molecular data (nuclear ribosomal ITS region, mitochondrial cytochrome c oxidase subunit I and nuclear histone 3 gene sequences). Apart form the new species, GenBank reference sequences are provided for the first time for F. hegemon and F. regularis. The results show that, although the shape of the spermatheca is a very important marker in the case of Fridericia species, other characters can be equally important for their taxonomic identification.